PENGARUH KUALITAS PELAYANAN PRAMUWISATA LOKAL TERHADAP KEPUASAN WISATAWAN MANCANEGARA DI CANDI PRAMBANAN - Ahmad Irfan Setiawan; I Made Sendra; I Putu Sudana (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
Prambanan is the biggest Hindu temple in Indonesia, this temple already recognized by UNESCO as one of word heritage. One of the human resources supporting the attraction of the Prambanan Temple is local guide. The purpose of this research is to know influence of service quality local guide towards satisfaction for foreign tourist. This location of this research at Candi Prambanan with 190 respondent, for sample it use purposive sampling method. The data collect by kuisioner which spread to the guest after finish tour with the local guide. Analysis that used in this research is multiple regression with instrument by SPSS 17.0. The results from this research is: 1) Service Quality dimension tangible is influence towards the Satisfaction with point of Sig. 0.037 2) Service Quality dimension empathy not have influence towards the satisfaction with point of Sig. 0.226 3) Service Quality dimension responsiveness individually not have influence towards the Satisfaction with point Sig. 0.290 4) Service Quality dimension reliability have influence towards satisfaction with point Sig 0.02 5) Service Quality dimension assurance have influence towards satisfaction with point of Sig 0.000 6) Service Quality with all dimension (tangible, empathy, responsiveness, reliability, assurance) have influence towards satisfaction.